Faktor-faktor yang Mempengaruhi Kekambuhan pada Pasien Skizofrenia di RSD dr. Soebandi Jember (Factors that Affect the Recurrence of Schizophrenia at dr. Soebandi Hospital, Jember) - Farida Yan Pratiwi Kurnia; Justina Evy Tyaswati; Cholis Abrori (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Schizophrenia is one of the health problems in developing countries and developed countries. Risk factors that may affect the reccurrence of schizophrenia consist of internal and eksternal factors. The purpose of this study was to analyze the factors which affect the recurrence of schizophrenia. This study was a quantitative research with cross sectional approach. Sample in this study was obtained by total sampling from family of schizophrenia patients who visited Polyclinic Psychiatry dr. Soebandi Public Hospital of Jember. The factors studied were age, gender, education, occupation, economic condition, schizophrenia onset, type of schizophrenia, family's knowledge, character of family, character of paramedic, physic factor, disobedience medication, and type of medication . Data analysis was performed by chi square test and logistic regression. Chi square test found a significant factor that was age (p=0.029), schizophrenia onset (p=0.037), physical factor (p=0,022), and disobedience medication (p=0.021) while other factors did not significant. Results of logistic regression test results obtained for age was (p=0.019, OR=0.279), schizophrenia onset (p=0.068, OR=0.224), character of family (p=0.035, OR=0,214) and to disobedience medication (p=0.013, OR=4,064). It can be concluded that the most factor that affect the recurrence of schizophrenia was disobedience medication. Keywords: recurrence, schizophrenia